From untouchable to Dalit : essays on the Ambedkar movement - Zelliot, Eleanor (Manohar Publications, 1992)
On the Dalit Movement started by Bhimrao Ramji Ambedkar, 1892-1956, Indian statesman and social reformer, in Maharashtra.